Implications of defects in building condition of heritage mosques in Perak / Ahmad Hafidzullah Zulkifli and Nurhidayah Samsul Rijal - Zulkifli, Ahmad Hafidzullah; Samsul Rijal, Nurhidayah (2023)
Preserving and maintaining heritage buildings, including mosques, is crucial to ensure their continued functionality and benefits for all age groups in Malaysia. Some mosques in Malaysia have been recognized as heritage monuments under the National Heritage Act of 2005 (Act 645) due to their historical significance. Defects in heritage buildings not only diminish the level of comfort but also impact the structural integrity of such buildings, potentially leading to injuries and compromising their overall quality and performance. Therefore, it is essential to investigate the types of defects present and their implications on the building condition of heritage mosques located in Ipoh, Perak. For purposes of this research, three heritage mosques were selected based on their distinct characteristics. A qualitative research design was employed, involving interviews with the mosque management. Each case study required two respondents to partake in the interview sessions. Using the Building Condition Assessment (BCA) method, it was determined that 18% of the total defects in the three selected heritage mosques were related to cracks. Specifically, the India Muslim Mosque accounted for 14% of the cracks, Kampung Paloh Mosque accounted for 2%, and the remaining percentage of the cracks are found at Dato’ Panglima Kinta Mosque. The significance of this study lies in identifying the types of defects prevalent in heritage mosques and determining the effectiveness of the BCA method in minimizing these issues. The findings will be valuable to mosque management, aiding them in maintaining these cultural and historical landmarks for future generations.